The Unequal Effects of Liberalization: Evidence from Dismantling the License Raj in India - Aghion, Philippe; Burgess, Robin; Redding, Stephen J; Zilibotti, Fabrizio (American Economic Review, 2008)
We study whether the effects on registered manufacturing output of dismantling the License Raj—a system of central controls regulating entry and production activity in this sector—vary across Indian states with different labor market regulations. The effects are found to be unequal across Indian states with different labor market regulations. In particular, following delicensing, industries located in states with pro-employer labor market institutions grew more quickly than those in pro-worker environments. (JEL J50, L52,L60, O14, O15, O25)